2002
DOI: 10.1097/00007632-200203010-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Psychological Factors as Predictors of Chronicity/Disability in Prospective Cohorts of Low Back Pain

Abstract: Psychological factors (notably distress, depressive mood, and somatization) are implicated in the transition to chronic low back pain. The development and testing of clinical interventions specifically targeting these factors is indicated. In view of the importance attributed to other psychological factors (particularly coping strategies and fear avoidance) there is a need to clarify their role in back-related disability through rigorous prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

47
853
2
39

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,422 publications
(941 citation statements)
references
References 49 publications
47
853
2
39
Order By: Relevance
“…Age is a potential confounder in the relationship between depression and LBP and should be accounted for. In fact, when studies that investigated older participants only (6,13,14) were pooled, a stronger association was found (OR 1.98, 95% CI 1.40-2.81, I 2 5 51%) compared to the overall pooling of primary analysis (OR 1.59, 95% CI 1.26-2.01, I 2 5 59%). It is likely that depression might have a stronger effect in increasing the risk of LBP in older people, but the factors that explain this relationship are still unclear.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Age is a potential confounder in the relationship between depression and LBP and should be accounted for. In fact, when studies that investigated older participants only (6,13,14) were pooled, a stronger association was found (OR 1.98, 95% CI 1.40-2.81, I 2 5 51%) compared to the overall pooling of primary analysis (OR 1.59, 95% CI 1.26-2.01, I 2 5 59%). It is likely that depression might have a stronger effect in increasing the risk of LBP in older people, but the factors that explain this relationship are still unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have found depression to be associated with an increased risk of developing LBP (6)(7)(8), while other studies have failed to show a significant association (9)(10)(11). Previous reviews investigating the role of psychological variables in LBP have shown evidence of depression as a predictor of poor outcomes, such as chronicity, disability, and work absenteeism (12)(13)(14). However, these reviews did not specifically focus on premorbid depression as a risk factor for new cases of LBP.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] FAB refer to the fear-induced avoidance of movements or activities which are expected to be painful, whereas catastrophizing is defined as an exaggerated negative mental state related to an actual or anticipated painful experience. [1][2][3][4][5][6][7][8][9] In the Spanish cultural environment, FAB have shown to have an either negligible or nonexistent influence on LBP among elderly populations and among acute, subacute and chronic LBP patients treated in routine practice, [10][11][12][13] whereas catastrophizing correlates with disability and explains approximately one fourth of its variance, 13,14 suggesting that it may have an influence on the prognosis of LBP patients.…”
Section: Introductionmentioning
confidence: 99%
“…Exhaustive research has failed to find a correlation between pain, structural damage in the spine and the level of disability in non-specific LBP [2,3]. Among the factors that predict disability and chronicity from LBP, patients' beliefs about fear-avoidance, pain-impairment relationship and coping strategies are strongly associated with outcome from treatment [4,5]. Accordingly, a biopsychosocial model has been proposed to explain the process through which LBP causes disability and tends to become chronic.…”
Section: Introductionmentioning
confidence: 99%